2006
DOI: 10.1088/0034-4885/69/5/r05
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic compression of materials: metallization of fluid hydrogen at high pressures

Abstract: Dynamic high pressure is 1 GPa (10 kbar) or greater with a rise time and a duration ranging from 1 ps (10 −12 s) to 1 µs (10 −6 s). Today it is possible in a laboratory to achieve pressures dynamically up to ∼500 GPa (5 Mbar) and greater, compressions as much as ∼15fold greater than initial density in the case of hydrogen and temperatures from ∼0.1 up to several electronvolts (11 600 K). At these conditions materials are extremely condensed semiconductors or degenerate metals. Temperature can be tuned independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
118
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(119 citation statements)
references
References 326 publications
(472 reference statements)
1
118
0
Order By: Relevance
“…Simulations have shown that using the SIS100 parameters, it is possible to compress solid hydrogen to a density of about 3g/cm 3 having a pressure of the order of 30 Mbar while the temperature remains low (about 10000 K) which are conditions expected at the interiors of the Gaint palnets. This experiment can also help to understand hydrogen metallization [10] problem.…”
Section: Multiple Reflection Of Cylindrical Shocks and The Laplas Schemementioning
confidence: 93%
“…Simulations have shown that using the SIS100 parameters, it is possible to compress solid hydrogen to a density of about 3g/cm 3 having a pressure of the order of 30 Mbar while the temperature remains low (about 10000 K) which are conditions expected at the interiors of the Gaint palnets. This experiment can also help to understand hydrogen metallization [10] problem.…”
Section: Multiple Reflection Of Cylindrical Shocks and The Laplas Schemementioning
confidence: 93%
“…We assume that, when metallic hydrogen is produced, the molecular phase of liquid hydrogen transforms into the atomic phase [9] and only some atoms are later ionized.…”
Section: Metal-dielectric Transitionmentioning
confidence: 99%
“…A qualitative breakthrough in the studies of metallic hydrogen occurred after a number of experiments on shock compression of both molecular hydrogen in the liquid state and hydrogen and deuterium plasma. Those experiments showed that electric conductivity increased steeply for certain combinations of density, pressure, and temperature [4][5][6][7][8][9]. Specific values of these parameters depended on the initial state of hydrogen (i.e., the state before compression).…”
Section: Introductionmentioning
confidence: 99%
“…Material-strength changes and phase transitions occur on nanosecond time scales in impact experiments -on these short time scales, the response of materials can be remarkably different than expected when compared to slower loading. The different macroscopic dynamics observed under high load rates has inspired theories that attempt to predict the underlying rates of microscopic mechanisms responsible for the observed differences in behavior (for recent reviews, see [1][2][3][4][5]). …”
Section: Introductionmentioning
confidence: 99%
“…Mass velocities up to a few km/s are generated in single-shock, propellant-driven, flier-plate impact experiments [1][2][3]. Higher velocities have been generated in pulsed-laser and pulsed-plasma driven experiments up to 19 km/s [6], 30 km/s [4], and ~ 100 km/s [5]. Improving the temporal and velocity resolution of high-velocity measurements continues to be of interest as it will lead to improved data needed to better understand high strain rate processes.…”
Section: Introductionmentioning
confidence: 99%